Engineering Design Business Process Modelling Letter C Land Data Archiving System with Software Requirement Specifications Approach - Santi, Indyah Hartami; Febrinita, Filda; Puspitasari, Wahyu Dwi (Institute of Computer Science (IOCS), 2023)
The Pandanarum Village area includes three hamlets, namely Pandanarum, Klampok and Sentul. The status of village land ownership rights is still in the form of Letter C. In 2023, land ownership will be recorded at more than 4,000. The process of collecting data, searching and changing Letter C is still done manually by recording it in the Letter C main book (Registration Book C). Meanwhile, the search process was carried out by flipping through the master book, which resulted in the book becoming torn and damaged. Almost every day some people need services regarding the letter C land data. With a manual process, recording and searching for data takes an average of 2-3 days. This is an obstacle for people who want this data urgently. The solution offered is the need to engineer a village letter C data collection and search system with business process modeling. System development is carried out using the Software Development Life Cycle (SDLC). In this research, the focus is on the initial stage of SDLC, namely Requirements with a Software Requirement Specification (SRS) approach following IEEE standards. This research aims to engineer a business model for data collection and land Letter C searches with the hope of improving the services of village officials in response to requests from the community who need services for data collection, search and changes to land rights they own. The results of this research are the identification of functional and non-functional system requirements analysis, system design in the form of business process models and use case diagrams. The results of this requirements design become the basis for continuing subsequent research.